A genetic element in the SARS-CoV-2 genome is shared with multiple insect species. (11th March 2021) - Tengs, Torstein; Delwiche, Charles F.; Monceyron Jonassen, Christine
Abstract : SARS-CoV-2 is a member of the subgenus Sarbecovirus and thus contains the genetic element s2m. We have extensively mined nucleotide data in GenBank in order to obtain a comprehensive list of s2m sequences both in the four virus families where s2m has previously been described and in other groups of organisms. Surprisingly, there seems to be a xenologue of s2m in a large number of insect species. The function of s2m is unknown, but our data show a very high degree of sequence conservation both in insects and in viruses and that the version of s2m found in SARS-CoV-2 has unique features, not seen in any other virus or insect strains.